A young man with chronic dry cough - Shalihin, Mohd Shaiful Ehsan; Osman, Iskandar Firzada; Harun, Zulkifli; Mukhali, Hassan Basri; Gnathimin, Bari (2020)
In primary care, chest X-rays are commonly performed to assess patients presenting with a prolonged cough. However, the extent to which the films are accurately interpreted depends on the skill of the doctors. Doctors with insufficient experience may miss an exact diagnosis when evaluating a film, especially in patients with nonspecific symptoms, such as in the case discussed in this paper. This case involved a persistent dry cough with an underlying diagnosis that would have been missed if the findings of the chest X-ray had not been properly analyzed